AKUNTANSI PERNIKAHAN DI PULAU LOMBOK - Muhammad Ali Fikri; Nina Karina Karim; W Widyastuti (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2016)
The objective of this study is to analyze marriage from the accounting perspective. This study examined whether a husband (wife) was recognized as revenues, expenses, assets, or liabilities. Using a sample of 20 people as respondents on Lombok island community who have experienced divorces, the study conclude that marriage is regarded as expense and liabilities, instead of income or assets. Keywords: marriage, assets, revenues, expenses, liabilities